Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share untuk Meningkatkan Hasil Belajar IPAS bagi Peserta Didik Kelas IV Madrasah Ibtidaiyah Negeri 2 Kabupaten Tebo - Tri Anggraini; Ika Aryastuti Hasanah (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to analyze the application of the Think Pair Share type cooperative learning model to improve science learning outcomes for Class IV Students of Madrasah Ibtidaiyah Negeri 2 Tebo Regency. This research is classroom action research carried out in two cycles. The subjects of this research were Class IV students of Madrasah Ibtidaiyah Negeri 2 Tebo Regency. This research was carried out in the second semester of the 2024/2025 academic year in Class IV of Madrasah Ibtidaiyah Negeri 2 Tebo Regency. The results of this research are (1) the application of the Think Pair Share Type Cooperative Learning Model to improve the learning process of Class IV MIN 2 Tebo Regency students, carried out through the planning, implementation and evaluation stages of learning, (2) the application of the Think Pair Share Type Cooperative Learning Model (TPS) can improve the science learning outcomes of Class IV students as seen from the increase in teacher observation data from the average value of Cycle I, namely 78.12 in the